2015
DOI: 10.1055/s-0035-1559886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetylserotonin on Intestinal Recovery Following Intestinal Ischemia–Reperfusion Injury in a Rat

Abstract: Treatment with NAS prevents gut mucosal damage and inhibits programmed cell death following intestinal IR in a rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Moreover, NAS has been approved by the FDA for treatment of neurological disorders and stroke [29]. Recent studies have shown that NAS protects against oxidative damage in neurons, erythrocytes, retinal cells, lung epithelial cells, lymphocytes, and enterocytes [17,[29][30][31][32]. However, the underlying mechanisms responsible for the beneficial effect of NAS are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NAS has been approved by the FDA for treatment of neurological disorders and stroke [29]. Recent studies have shown that NAS protects against oxidative damage in neurons, erythrocytes, retinal cells, lung epithelial cells, lymphocytes, and enterocytes [17,[29][30][31][32]. However, the underlying mechanisms responsible for the beneficial effect of NAS are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro studies have shown that NAS has a more potent antioxidant capacity than melatonin [15]. NAS administration protects ischemia-reperfusion-induced mucosal damage in the jejunum and ileum of rats [17]. About 25% of dietary Trp is degraded by the porcine small intestine during its first pass into the portal vein and leads to the generation of multiple metabolites including serotonin, melatonin, and NAS [18].…”
Section: Introductionmentioning
confidence: 99%
“…While 5-HT predominantly exerts proinflammatory effects, emerging evidence points to the anti-inflammatory and anti-oxidant effects of its endogenous fatty acid-conjugates, Nacyl 5-HTs, present in the gut [38][39][40][41]138]. Our laboratory uncovered that docosahexaenoylserotonin (DHA-5-HT), the conjugate of 5-HT with the n-3 poly unsaturated long chain fatty acid (LC PUFA) DHA, has anti-inflammatory effects both in mouse macrophages as well as in human peripheral blood mononuclear cells (PBMCs), by attenuating release of key inflammatory mediators [40,41].…”
Section: Fatty Acid-5-ht Conjugates With Immune-modulatory and Anti-omentioning
confidence: 99%
“…Furthermore, N-acyl-5-HTs with varying fatty acid moieties were reported to exert anti-inflammatory, anti-oxidant, and neuroprotective effects in a number of in vivo animal disease models [38,39,[142][143][144][145]. In an inflammatory in vivo gut model, the SCFA conjugate of 5-HT, N-acetyl-5-HT (also called NAS), has been shown to prevent gut mucosal damage and inhibit programmed cell death following intestinal ischemia-reperfusion (IR) in rats [38]. Intestinal IR is a multifactorial pathophysiological process involving nonspecific damage of the gut, which can occur during trauma, sepsis, or shock.…”
Section: Fatty Acid-5-ht Conjugates With Immune-modulatory and Anti-omentioning
confidence: 99%
See 1 more Smart Citation